(untitled) (Ágora de Heterodoxias, 2025)
The present research confirms that companies that improve their environmental performance also improve their economic performance, by collecting, analyzing and interpreting information from 2018 to 2022 of 19 of the 35 listed companies that in April 2021 were part of the S&P/BMV IPC Index of the Mexican Stock Exchange, through the calculation of the "eco-efficiency formula" and the obtaining of the eco-efficiency index of CO2 emissions. With this, it is intended to contribute to the development of an experimental framework of the Theory of Eco-efficiency, through a documentary study with the financial and sustainability reports published by the same companies.